2007
DOI: 10.5194/angeo-25-2125-2007
|View full text |Cite
|
Sign up to set email alerts
|

Wind profiler observations of a monsoon low-level jet over a tropical Indian station

Abstract: Abstract. Three-year high-resolution wind observations of the wind profiler have been utilized to characterize the diurnal and seasonal features of the monsoon Low-Level Jet (LLJ) over a tropical station, Gadanki (13.5 • N, 79.2 • E), with a focus on the diurnal variability of low-level winds. The Boreal summer monsoon winds show a conspicuously strong westerly LLJ with average wind speed exceeding 20 m s −1 . The L-band wind profiler measurements have shown an advantage of better height and time resolutions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 25 publications
(30 reference statements)
3
12
0
Order By: Relevance
“…Overall, the occurrence distribution of LLJ shows a diurnal change, and the similar results have been indicated in Kalapureddy et al . []. Both Tianjin and Shanghai display a similar pattern.…”
Section: Llj Characteristicsmentioning
confidence: 88%
“…Overall, the occurrence distribution of LLJ shows a diurnal change, and the similar results have been indicated in Kalapureddy et al . []. Both Tianjin and Shanghai display a similar pattern.…”
Section: Llj Characteristicsmentioning
confidence: 88%
“…Using lower atmospheric wind profiler (LAWP) data over Gadanki, India, Kalapureddy et al . [] showed that the MLLJ core lies at a height of 1.8 + 0.6 km with a mean jet intensity of about 20 m/s. Using measurements from a UHF radar/wind profiler (404 MHz) over Pune (18.38°N, 73.58°E), India, Joshi et al .…”
Section: Introductionmentioning
confidence: 99%
“…Before going into further detail, it is worthwhile to see how much diurnal variation exists in the MLLJ intensity and height. Although the diurnal variation of the MLLJ is least explored, by considering the diurnal cycle measured with UHF radar over Gadanki Kalapureddy et al (2007) showed that the MLLJ exhibits strong diurnal variability in intensity and height of the jet core, with its core peaking up to 3 km during 0900-2200 LT. In the present study, the GPS radiosonde measurements and other reanalysis datasets over Gadanki have been considered to study the diurnal variation of MLLJ.…”
Section: B Diurnal Variation Of the Mllj Over Gadankimentioning
confidence: 99%
“…Using Lower Atmospheric Wind Profiler (LAWP) data over Gadanki, Kalapureddy et al (2007) showed that the MLLJ core lies at a height of 1.8 6 0.6 km and found the mean jet intensity to be 20 m s 21 . Using a similar instrument over Pune (18.38N, 73.58E), Joshi et al (2006) found that the jet core height varies between 1.6 and 3 km.…”
Section: Introductionmentioning
confidence: 99%